Tinjauan Kemampuan Forehand Drive Komunitas Tenis Lapangan UNIMED - Gulasa Octo Gilbert Sihombing (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
The purpose of this study was to determine the level of forehand drive ability of the UNIMED tennis community under the conditions as it is without any prior special treatment. This research is a descriptive research. The population in this study amounted to 15 people with total sampling using total sampling, which means that the entire population of 15 people became the sample in this study. The instrument in this study used the Hewitt tennis achievement test forehand drive to measure the forehand drive ability. Based on the tests carried out, the results of the forehand drive ability were obtained with an average value of 15.46. The average results obtained from each athlete illustrate that the forehand drive ability of the UNIMED tennis community is in the sufficient category. One of the factors causing the low forehand drive ability is the athlete's error in doing footwork. These results indicate that it is necessary to carry out regular and continuous exercises to improve the forehand drive ability, one of which is footwork exercises.